Communes and conflict : urban rebellion in Late Medieval Flanders. - Dumolyn, Jan; Haemers, Jelle, 1980-; Murray, Andrew; Van den Maagdenberg, Joannes (Leiden: Brill, 2023)
"In Communes and Conflict, Jan Dumolyn and Jelle Haemers explore the urban rebellions that regularly erupted in Flanders between the thirteenth and sixteenth centuries. They analyse not only how these rebellions were sparked and repressed, but also how they shaped the culture and identity of Flemish townspeople. Drawing from a wide range of theoretical methods and concepts, including those of discourse analysis, semiotics, speech acts, collective memory and material cultural studies, the authors return to key Marxist questions on ideology, labour and class interest to map the perspectives of the rebels, the urban patriciate and the Flemish and Burgundian nobility"
boek
Keywords: Cities and towns, Medieval -- Belgium -- Flanders; Social classes -- Flanders -- History -- To 1500.; Flanders -- History -- To 1500.; Flanders -- Politics and government -- To 1500.